Recreate Reality: the Emergence of Ethnographic Film at the Academy (Andamios, Revista de Investigación Social, 2014)
This paper discusses the emergence of ethnographic film in the academy as a conceptual encouragement for Anthropology and identifies resistances to quality filmmaking framed in this discipline. It argues that ethnographic filmmaking should put the specificity of film activity before any pedagogical or illustrative aims. In short, it believes that reality must precede the search for meaning.
Keywords: Anthropology; Documentary; Ethnographic Cinema; Meaning; Reality